Persistent symptomatic parvovirus B19 infection with severe thrombocytopenia transmitted by red blood cell transfusion containing low parvovirus B19 DNA levels. Issue 6 (2nd April 2017) - Nagaharu, Keiki; Sugimoto, Yuka; Hoshi, Yuji; Yamaguchi, Takanori; Ito, Ryugo; Matsubayashi, Keiji; Kawakami, Keiki; Ohishi, Kohshi
Abstract : BACKGROUND: Transfusion‐mediated human parvovirus B19 (PVB19) infection is rare but often causes severe hematologic disorders. In Japan, routine blood donor screening for PVB19 antigen (detection sensitivity, 10 6.4 IU/mL) using a chemiluminescent enzyme immunoassay (CLEIA) was introduced in 2008. However, there is no consensus on the minimal infectious dose of PVB19 permissible for red blood cells (RBCs). CASE REPORT: A 64‐year‐old man, who had received hemodialysis for diabetic nephropathy for 5 years, underwent an RBC transfusion for anemia caused by hemorrhagic enterocolitis. He developed persistent high fever and progressive thrombocytopenia. He was diagnosed with PVB19 infection when a marrow examination showed giant erythroblasts, and his serum was positive for PVB19 DNA. His serum was negative for PVB19 immunoglobulin (Ig)M and IgG before transfusion, but positive for both after transfusion. This PVB19 infection was deemed to be transmitted by the RBC transfusion because low levels of PVB19 DNA (1.10 × 10 4 IU/mL) were detected in one of the blood donors. A DNA homology test of PVB19 showed complete genomic identity between the virus in the donor and our patient. CONCLUSION: We report a patient who developed persistent PVB19 infection from an RBC transfusion containing low levels of PVB19. This is the second case of transfusion‐mediated PVB19 infection since the introduction of CLEIA in 2008. Transmission may occur in immunocompromised patients lacking PVB19‐neutralizing antibodies. The report of further such cases will allow the establishment of minimal threshold values and more effective screening tests for PBV19 transmission through RBC products.